Congenital Myasthenic Syndrome Caused by a Novel Hemizygous CHAT Mutation - Zhang, Yixia; Cheng, Xinru; Luo, Chenghan; Lei, Mengyuan; Mao, Fengxia; Shi, Zanyang; Cao, Wenjun; Zhang, Jingdi; Zhang, Qian (Frontiers in Pediatrics, 2020)
Congenital myasthenic syndrome (CMS) is a neuromuscular transmission disorder caused by mutations in genes encoding neuromuscular junction proteins. CMS due to choline acetyltransferase (CHAT) gene mutation is characterized by episodic apnoea. To date, 52 cases of CMS caused by CHAT gene mutations have been reported. Here, we report a neonate with the third hemizygous mutation (a 4.9 Mb deletion (10q11.22-10q11.23 (chr10: 46123781-51028772)) containing the whole CHAT gene and c.1976A>T (p.Gln659Leu in the CHAT gene)). The c.1976A>T (p.Gln659Leu) variant had not been reported in the ExAC or gnomAD databases and was predicted to be pathogenic. The alignment of amino acid sequences revealed that glutamine at codon 659 is highly conserved in different species and causes structural changes in the substrate-binding site. Our female patient with neonate-onset CMS presented with apnoea, dyspnoea, feeding difficulties, weak crying, and seizure-like episodes, and her respiration was ventilator dependent. The prostigmine test was positive. This case may help to further elucidate clinical features and treatment methods in neonate-onset CMS caused by CHAT gene mutations.